Reperfusion of Acute Myocardial Infarction in the elderly (clinical characteristics and prognosis) Results of the IMSS Nuevo León infarction code program - Zapata Ruiz Alejandro; Palacios R Juan Manuel; De la Cruz O Ramón; Arboine A Luis; Sierra F Ángel; Muñoz Consuegra Carlos (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Background: The age is an important prognostic factor in patients with acute myocardial infarction. To find no similar data in the Mexican population, it seeks to establish the characteristics and prognosis of older adults carried out mechanical reperfusion treatment. Methods and results: We carried out a retrospective analysis included a total of 1025 patients in the program code myocardial reperfusion treatment carried out, being the 15.3 % over the age of 75 years. The age range of 33 to 92 years. The mortality rate is increasing exponentially higher age (3.4 % for patients <= 54 years, 6.1% for 55 to 64 years, 9.2% for 65 to 75 years and 15.9 % for the >= 75 years, p<0,001) in patients older than 75 years, primary angioplasty is the preferred method of reperfusion (77.7 %), without finding in this group of patients, an increase in the cerebral vascular event ischemic or hemorrhagic. Over the age of 75 years who develop cardiogenic shock have a much higher mortality compared with the younger (17.6%, 28%, 33% vs 56%, p<0.001). Conclusions: Despite the different treatments of reperfusion, mortality remains higher in older adults, mainly by multiple comorbidities and a higher rate of ventricular dysfunction.